Learning Style-Based Learning Tools to Improve Higher-Order Thinking Skills in IPAS Learning - Prastiyono; Joko Siswanto; Sumarno (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
The science learning process in elementary schools still tends to use a uniform approach, so it is unable to accommodate differences in student learning styles. This condition causes students' higher-order thinking skills (HOTS). This study aims to develop differentiated learning tools tailored to learning styles to improve students' higher-order thinking skills (HOTS) in learning (IPAS) in grade IV elementary schools. This research is motivated by students' low analytical, evaluative, and creative abilities due to a learning process that remains uniform and does not accommodate differences in individual learning styles, namely visual, auditory, and kinesthetic. This type of research is research and development (R&D) using the 4D model. The research subjects involved 27 grade IV elementary school students. Data were collected through expert validation sheets, observation of learning activities, high-order thinking ability tests, and teacher and student response questionnaires. The results showed that the developed learning tools met the criteria of very valid (91.25%), very practical (90.4%), and very effective, with an N-gain value of 0.84. Based on these results, it can be concluded that integrating learning styles into differentiated instruction effectively improves students' analytical and creative abilities in science. The implications of this research indicate that differentiated learning tools can be a practical, adaptable model for teachers in implementing student-centered learning in line with the objectives of the Independent Curriculum in elementary schools.